Professional Development Altogether: Pre-Service and In-Service EFL Teacher Collaboration in Doing Classroom Action Research - Ridwan, Arfiyan; Athena, Tera (Universitas Lancang Kuning, 2023)
Classroom action research is one of the way pre-service and in-service teachers performed professional development in classroom research to gain better quality of teaching- with different portion and ways. This research deliberates the outcome of a case study involving an Indonesian in-service teacher in a collaborative action research with one pre-service teachers from a college of Education, STKIP PGRI Bangkalan, during an internship period. They worked on the classroom problems found during internship term and attempted to find the way to overcome them through technology integration in the instruction. Five open-ended questions were given to the in-service teacher and the pre-service teacher. With qualitative data analysis, the research found some significant results: 1) The in-service teacher felt more helped in utilizing technology, especially in the use and making of podcast for teaching listening. The teacher’s years of experience in handing teaching learning process in the class compiled the pre-service teacher’ competence as a novice teacher. (2) On the other side, the in-service teacher, felt more helped in getting fresh idea of teaching EFL, especially with the technology utilization. Challenges from both perspectives were also found in terms of workload, internship duration, feedbacks, digital literacy, pedagogical belief, and publication. Overall, professional development has been achieved by the two kinds teacher, and one of the means of doing that is through collaborative action research.